Road Map for a Transboundary Haze-Free ASEAN by 2020: Time to Implement Agreement - Raman Letchumanan (2015)
As the ASEAN Summit approaches, we explore a set of integrated solutions, which if implemented with full commitment and vigour, can progressively minimise by 2020 severe crises of transboundary haze pollution such as being experienced now.